Custom made orthotic device for maintaining skull architecture during the postoperative period in infants undergoing craniosynostosis surgery - Venu Gopal; Praveen Ganesh; Muralidhara Nagarjuna; Kiran Kumar; Samarth Shetty; Paul C. Salins (Elsevier, 2015)
Aim: To fabricate a cost effective, indigenous and simple orthotics helmet for post-operative cranial molding in patients with craniosynostosis surgery. Methods: We present a case of 15 month old infant with secondary cranial vault deformity. Cranial vault remodeling surgery involving the posterior skull was planned and executed to increase the posterior gap, so that brain growth would be facilitated towards this empty space. Materials such as thermoplastic sponge, thermoplastic ionomer resin sheet, soft sponge and Velcro straps are used to fabricate a cranial orthotics helmet. Results: We have successfully used the above materials to fabricate the orthotics helmet for post-operative cranial molding. Conclusion: The technique described in this article is simple and cost effective. It can be custom made according to the demands of the surgical technique and the type of synostosis. It favors an individualistic prognosis, and proves worthwhile as every synostosis requires a unique treatment plan. It is an excellent adjuvant to craniosynostosis remodeling surgery.